The Picture of Dorian Gray : la passion du réel/la passion du semblant - Annie Ramel (Cahiers Victoriens et Edouardiens)
Slavoj Zizek has recently argued that the 20th century is characterized by the « passion for the real, » which is an exact inversion of the passion for semblances : beneath our modern passion for virtual reality there lurks a longing for « the experience of the real world of material decay ». The Picture of Dorian Gray was written in a period of transition between the 19th century and the 20th, and my point is that Wilde’s aestheticism must be re-appraised in the light of Zizek’s thought. A study of doors and windows in the novel shows that Dorian commits a major transgression which consists in mistaking the « window » of fantasy for a « door » that leads beyond the pleasure principle and provides « the thrill of the Real ». Dorian’s passion is not so much for beauty and art, but for the decomposing portrait, its grey and amorphous matter, the « palpitating life substance prior to symbolic mortification » from which he derives exquisite enjoyment.